Cardiovascular complications of calcium supplementation in chronic kidney disease: are there arrhythmic risks?. (September 2014) - Genovesi, Simonetta; Gallieni, Maurizio
<x xml:space="preserve">Abstract</x> Calcium supplements may induce hypercalcaemia in patients with chronic kidney disease (CKD) or patients on hemodialysis. Even in the absence of overt hypercalcaemia, calcium supplementation may be associated with a positive calcium balance and intracellular calcium overload. There is an increased risk of complex supraventricular, ventricular arrhythmias or the risk of suffering a cardiac arrest in the presence of hypercalcaemia and calcium overload in subjects with impaired or absent renal function. A maximum intake of 1000 mg elemental calcium, combining supplements and dietary calcium, together with a 1.5 mmol/l level in the dialysate, may be a safer (opinion based) recommendation in CKD patients. This is especially the case if the patient already shows signs of extra-skeletal calcification or if they present cardiac comorbidities. Lower calcium levels in the dialysis fluid might reduce the positive calcium balance but can increase intradialytic plasma calcium changes and therefore increase the risk of arrhythmias.